2002
DOI: 10.3987/com-02-9479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Base, Electrophile, and Substrate on the Selective Alkylation of Heteroaromatic Systems

Abstract: Several heteroaromatic systems, including oxazoles, pyrazoles, and thiophenes, are regioselectively alkylated using lithium diethylamide. Effects of substrate, base, and electrophile on the selectivity of this process are surveyed and interpreted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, deprotonation of 2-methyl-4-phenyloxazole ( 10 ) using n -BuLi at −78 °C followed by alkylation with methyl iodide gives a 14:86 ratio of products ( 13 : 14 ) favoring ring methylation, while the use of LiNEt 2 leads to alkylation solely at the C 2 -methyl site. This reversal of regioselectivity is thought to arise from the ability of diethylamine to mediate the low-temperature equilibration of a kinetic mixture of otherwise noninterconverting lithiated intermediates ( 11 and 12 ) . Given these results, we thought it possible that the undesired C 13 -alkylation observed by Williams might be a consequence of kinetic (ring) deprotonation and that we might achieve the desired C 15 -alkylation on a bisoxazole system such as 6 by equilibrating to the thermodynamic (methyl) lithiated intermediate.…”
Section: Resultsmentioning
confidence: 98%
“…For example, deprotonation of 2-methyl-4-phenyloxazole ( 10 ) using n -BuLi at −78 °C followed by alkylation with methyl iodide gives a 14:86 ratio of products ( 13 : 14 ) favoring ring methylation, while the use of LiNEt 2 leads to alkylation solely at the C 2 -methyl site. This reversal of regioselectivity is thought to arise from the ability of diethylamine to mediate the low-temperature equilibration of a kinetic mixture of otherwise noninterconverting lithiated intermediates ( 11 and 12 ) . Given these results, we thought it possible that the undesired C 13 -alkylation observed by Williams might be a consequence of kinetic (ring) deprotonation and that we might achieve the desired C 15 -alkylation on a bisoxazole system such as 6 by equilibrating to the thermodynamic (methyl) lithiated intermediate.…”
Section: Resultsmentioning
confidence: 98%
“…11 In fact, Williams has shown that bisoxazole 4 is lithiated with n-BuLi exclusively at the C 5' -ring position, 12 suggesting that alkylation of 2 at C 15 may be problematic if R = H. Despite this result, previous work confronting a similar problem in the synthesis of phorboxazole, demonstrated that the regioselectivity of some oxazole deprotonations can be altered by the use of lithium diethylamide. 13 As elaborated in the preceding communication, 14 2-methyl-4-phenyloxazole (6) using n-BuLi at -78 °C followed by alkylation with methyl iodide gives a 14:86 ratio of products (7:8) favoring ring methylation, while the use of LiNEt 2 leads to alkylation solely at the C 2 -methyl site. This reversal of regioselectivity is thought to arise from the ability of diethylamine to mediate the low-temperature equilibration of a kinetic mixture of otherwise noninterconverting lithiated intermediates (9 and 10).…”
Section: Introductionmentioning
confidence: 92%